Theoretical analysis of the concept "personal coming into being" in psychology - Julia Voznyuk (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article is devoted to the issue of personal coming into being. The personal coming into being interested scientists of philosophy, psychology, pedagogy since ancient times. Theoretical analysis focused on the field of psychological thought. The center of all researches in psychology is a person, the identity, as the highest value. We found the features of approaches of researchers of classical psychology and domestic scientists. The issue of personal coming into being was the subject of scientific research S. Freud, A. Adler, K. Lewin, C. Horney, A. Maslow, C. Rogers, L. Vyhotskiy, E. Erickson, G. Kostyuk, A. Nikitin, N. Harlamenkova, O. Bezkorovaina etc. We analyzed their views. We can generalize that the personal coming into being is a fundamental human need for self-disclosure and realization of per- sonal potential. This is one of the basic and very important personal needs. The personal coming into being is the human desire for a sense of own values and recognition. This requires a sufficient level of self-confidence, awareness of the goals and values of own live, adequate motivation. However, we can note that analysis of the concept of the personal coming into being needs constant attention, because of the development of the present, constant changes and the need to adapt to them.